2021
DOI: 10.1159/000512750
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor 21 Predicts and Promotes Vascular Calcification in Haemodialysis Patients

Abstract: <b><i>Background:</i></b> Cardiovascular disease (CVD) is the leading cause of death in haemodialysis (HD) patients. Vascular calcification (VC) is dramatically accelerated and is strongly associated with CVD events and mortality in HD patients. VC coexists with osteoporosis in many studies. Fibroblast growth factor 21 (FGF21) which is known as an adipocytokine is a new hypoglycemic strategy and is inversely related to bone mineral density. <b><i>Methods:</i></b>… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
(53 reference statements)
1
7
0
Order By: Relevance
“…[ 23 ] found that baseline FGF21 was an independent predictor of atherosclerotic cardiovascular disease via a survey of patients with atherosclerosis, and the risk of atherosclerotic cardiovascular disease was three times higher in patients with high FGF21 levels compared to patients with low FGF21 levels. Our preliminary results confirmed that serum FGF21 was a potential predictor and promoter of VC in patients undergoing MHD [ 12 ]. Because of the association of FGF21 with oxidative stress, inflammation, vascular calcification and atherosclerosis, it was reasonable to hypothesize that FGF21 was involved in the development of NIH and closely related to AVF functional patency loss.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…[ 23 ] found that baseline FGF21 was an independent predictor of atherosclerotic cardiovascular disease via a survey of patients with atherosclerosis, and the risk of atherosclerotic cardiovascular disease was three times higher in patients with high FGF21 levels compared to patients with low FGF21 levels. Our preliminary results confirmed that serum FGF21 was a potential predictor and promoter of VC in patients undergoing MHD [ 12 ]. Because of the association of FGF21 with oxidative stress, inflammation, vascular calcification and atherosclerosis, it was reasonable to hypothesize that FGF21 was involved in the development of NIH and closely related to AVF functional patency loss.…”
Section: Discussionsupporting
confidence: 77%
“…Second, elevation of FGF21 is an adaptive response to pathological conditions, but it cannot counteract the damage caused by multiple noxious stimuli, such as uremia. Third, FGF21 may be a potential pathogenic agent that aggravates AVF failure and accelerates mortality because it is associated with calcification and CKD-mineral and bone disorders [ 12 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been clinically associated with VC in hemodialyzed patients. Serum FGF21 has been highly correlated with high calcium scores in three different thoracic aorta segments: ascending thoracic aorta, aortic arch, and descending aorta ( 54 ). Additionally, FGF21 has been correlated with the increasing grade of aortic stenosis ( 55 ).…”
Section: Role Of Receptor Tyrosine Kinase In Cardiovascular Calcifica...mentioning
confidence: 99%